KEPEMILIKAN MANAJERIAL, KEBIJAKAN HUTANG, DAN RETURN ON EQUITY TERHADAP KEBIJAKAN DEVIDEN - Slamet Siswanto, 08.05.51.0086; Taswan, Taswan (Students Journal of Economic and Management, 2012)
This research is a study that examined the influence of managerial ownership, debt policy and the return on equity to dividend policy. The formulation of the problem in this study was to determine the effect of managerial ownership, debt policy, and return on equity of the dividend policy of either partially or simultaneously. The population in this research is a registered companyin Indonesia Stock Exchange. Determination of the sample in this study conducted purposive sampling criteria: companies that have issued financial statements for the period 2005-2009, and thecompany paying the dividends during the study period. Obtained a sample of 124 companies from 1085 companies listed on the Stock Exchange publishes the financial statements. The data is then tested to normality, multicolinearity, autocorrelation, and heteroscedasticity. The result data is normally distributed and free of symptoms classical assumptions. Hypothesis testing isperformed by t test and F test Based on data analysis and hypothesis testing shows that managerial ownership significantly and negatively related to dividend policy and debt policy (DER) have positive and significant impact on dividend policy, while ROE has positive and significant impact on dividend policy.Key words: dividend policy, managerial ownership, debt policy (DER), DER.